REPEATABILITY OF ACTION AS THE BASIS OF THE FUNCTIONAL-SEMANTIC FIELD, REPRESENTED BY VARIOUS LINGUISTIC MEANS - Sahakyan David Arsenovich (Academia Science Repository, 2023)
The article presents a fragment of the description of the functional-semantic field of the verbs of the modern Russian language, expressing the concept of "repeatability of action".The relevance of the study is determined by the postulate that the main task of the science of language is the study of linguistic signs, and the task of linguistic semantics is the study of the knowledge of these signs, and these signifieds must be distinguished at all important levels of the language: lexical, morphological, syntactic. In the grammatical system of the Russian verb, the aspect category occupies a central position. The complexity and diversity of this category led to its extensive and intensive development, which led to the creation of a separate branch of Russian studies-aspectology.